Solar PV energy system in Malaysian airport: Glare analysis, general design and performance assessment - S. Sreenath; K. Sudhakar; A .F. Yusop; E. Solomin; I. M. Kirpichnikova (Energy Reports, 2020)
There is a growing interest in airport-based solar plant installations around the world. The buffer zone area in airports can effectively be utilized by tapping solar energy. However, it possesses concern for air safety and navigation mainly from the possible glare of the PV array. The objective of the study is to analyze the technical performance of a proposed solar PV plant in the premises of Kuantan Airport, Malaysia using SolarGis software with due consideration of glare occurrence. Eight zones are selected, and it was observed that yellow glare will occur for 4,552 min at ATC from Zone 8. The impact of glare from the other zones is in accordance with FAA's glare policy. The selected zones cover 0.2677 km2 of the airport's land with solar potential of 20 MW. The proposed solar PV plant consists of 57,143 crystalline silicon PV modules. Each PV string consists of PV modules of 20 in number. The number of strings in the entire PV plant is 2,857. The proposed PV plant requires 40 numbers of central inverters and 20 numbers of transformers. The proposed solar PV power plant is expected to generate 26,304 MWh annually and this energy generation is 168 times the energy consumption of the airport's terminal building. The highest energy production will be observed in March (2,514 MWh). It is projected that the monthly average final yield varies from a maximum value of 125.70 MWh/MWp-month in March to a minimum of 90.70 MWh/MWp-month in December. The proposed solar plant in Kuantan airport is expected to perform sufficiently well with 76.88 % performance ratio and 15.22 % capacity utilization factor. These results predict the safe operation of the airport-based solar system in Malaysia without glare impact.
Keywords: 330; Airport; Glare; Performance; Photovoltaic; Solar; Simulation